2006
DOI: 10.1093/ps/85.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter and Salmonella Species on Farm, After Transport, and at Processing in Specialty Market Poultry

Abstract: The prevalence of Campylobacter and Salmonella spp. was determined from live bird to prepackaged carcass for 3 flocks from each of 6 types of California niche-market poultry. Commodities sampled included squab, quail, guinea fowl, duck, poussin (young chicken), and free-range broiler chickens. Campylobacter on-farm prevalence was lowest for squab, followed by guinea fowl, duck, quail, and free-range chickens. Poussin had the highest prevalence of Campylobacter. No Salmonella was isolated from guinea fowl or qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 31 publications
6
27
2
Order By: Relevance
“…Negative results for Salmonella spp. are in line with those recorded in a study conducted by McCrea et al (2006) in which no Salmonella was isolated from quail flocks examined.…”
Section: Discussionsupporting
confidence: 91%
“…Negative results for Salmonella spp. are in line with those recorded in a study conducted by McCrea et al (2006) in which no Salmonella was isolated from quail flocks examined.…”
Section: Discussionsupporting
confidence: 91%
“…Another study conducted in Iran recorded 15.55% prevalence rate of Salmonella in pigeons (Akbarmehr, 2010). Higher prevalence rate of Salmonella recorded in this study might be the effects of bird density, increased success of fecal-oral transmission, strain differences of the birds, immune status of the flocks and geographical variation (Carraminana et al, 1997;McCrea et al, 2006). Salmonella is known to cause food-borne infection in humans and estimated to cause 1.3 billion cases of gastroenteritis and 3 million deaths worldwide (Bhunia, 2008).…”
Section: Discussionmentioning
confidence: 86%
“…This study recorded the highest prevalence of Salmonella at the live bird markets (40.28%) as compared to farms (20%) and villages (30%). McCrea et al (2006) reported the lowest prevalence rate of Salmonella in squabs on farm (1.3%) compared to post transport squabs (2.1%) and carcass swabs of squabs (23.8%) in processing plants. Lack of proper hygiene and sanitary practices, cross contamination with other species of birds and overcrowding might be responsible for the highest prevalence of Salmonella in pigeons at the live bird markets.…”
Section: Discussionmentioning
confidence: 93%
“…Enhanced biosecurity measures may be particularly important at specific times of the year. Seasonality was an observed risk factor or a confounder of risk in many of the publications reviewed (5,7,11,25,35,40,41,44,46,48,53,54,65,68,69,77). The seasonal risk peak generally occurs in late summer/ early autumn, but the timing, extent, and sharpness of this peak can vary between countries and may be related to the latitude of the country (22).…”
Section: Resultsmentioning
confidence: 99%
“…Surveys of freerange flocks (organic or nonorganic) generally indicate a higher prevalence of colonization than in conventionally reared flocks (52,53,74). Free-range birds are also slaughtered at an older age than conventionally reared birds.…”
Section: Resultsmentioning
confidence: 99%